Human Capital, Infrastructure and Economic Growth in Arab World: A Panel Granger Causality Analysis - Edrees, A. (OMICS Group, 2016)
This study investigates the causal-relationships between human capital and economic growth, and between infrastructure and economic growth in Arab World countries. The study covers the period from 1974 to 2013 using annual data obtained from the World Bank. Most importantly, the study uses advanced Granger causality for panel data with fixed coefficients which introduced by Venet and Hurlin. The full sample has been divided into a sub-groups according the income level, namely, rich countries and non-rich countries, to check if there any existence of the structural differences. The results indicate that the causal-relationships between variables of interest are highly heterogeneous in Arab World. However, there is a feedback relationship between human capital and economic growth and between infrastructure and economic growth in the full sample countries and rich countries group. Also, the results found a oneway causality running from economic growth to human capital and infrastructure in non-rich countries group.
Keywords: Human capital; Infrastructure; Economic growth; Arab world; Granger-causality